Presence of Lutzomyia longipalpis and Nyssomyia whitmani in Entre Rios, Argentina - Santini, Maria Soledad (2018)
The objective of this study was to evaluate the presence of Lutzomyia longipalpis in the Argentine city of Concordia, in the province of Entre Rios, without record of this species despite previous samplings, but with canine cases of visceral leishmaniasis and Lu. longipalpis reports both, from Northern Argentine localities and from the city of Salto, Uruguay, located just across the river and the international border. This study confirms the presence of Lu. longipalpis and Nyssomyia whitmani, related to the risk of visceral and tegumentary leishmaniasis, respectively, in Concordia-Entre Rios. The presence of Lu. longipalpis confirms the ongoing dispersal along the Uruguay river basin. The presence of these species in the study area alerts about the risk of transmission of Leishmania spp.